2015
DOI: 10.3174/ajnr.a4375
|View full text |Cite
|
Sign up to set email alerts
|

Improving Multiple Sclerosis Plaque Detection Using a Semiautomated Assistive Approach

Abstract: BACKGROUND AND PURPOSE:Treating MS with disease-modifying drugs relies on accurate MR imaging follow-up to determine the treatment effect. We aimed to develop and validate a semiautomated software platform to facilitate detection of new lesions and improved lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 26 publications
(33 reference statements)
1
16
1
Order By: Relevance
“…11 A previous study has shown that a semiautomated assistive platform is fast, robust, and detects many more new lesions on MR imaging of patients with MS than conventional side-by-side comparison. 9 The same software has also been shown to perform similarly when used by readers of different radiology experience, including readers with minimal radiology experience. 12 This new approach allowed us to use it as a new "gold standard" against which we can measure the performance of radiologists of various levels of subspecialty experience.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…11 A previous study has shown that a semiautomated assistive platform is fast, robust, and detects many more new lesions on MR imaging of patients with MS than conventional side-by-side comparison. 9 The same software has also been shown to perform similarly when used by readers of different radiology experience, including readers with minimal radiology experience. 12 This new approach allowed us to use it as a new "gold standard" against which we can measure the performance of radiologists of various levels of subspecialty experience.…”
Section: Discussionmentioning
confidence: 98%
“…A semiautomated software package (VT) has previously been validated and shown to detect an increased number of new lesions in patients with MS compared with conventional side-by-side comparison. 9 The development of the software processing tool and data processing procedure has been described in that earlier study. All of the patients included in this study have been reported previously.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One approach to overcoming this problem is to extract lesion masks using a lesion segmentation algorithm 2 , which are subtracted to yield a lesion change mask. Alternatively, lesion change can be detected on the subtraction of two images either by humans 3 or with the help of an algorithm relying on the subtraction signal and lesion geometry 4 . While image subtraction can substantially improve lesion contrast, separating lesion change from background noise requires consideration of the statistical properties of the signal and noise.…”
Section: Introductionmentioning
confidence: 99%